Flexible room-temperature formaldehyde sensors based on rGO film and rGo/MoS2 hybrid film. (18th July 2017) - Li, Xian; Wang, Jing; Xie, Dan; Xu, Jianlong; Xia, Yi; Li, Weiwei; Xiang, Lan; Li, Zhemin; Xu, Shiwei; Komarneni, Sridhar
Abstract: Gas sensors based on reduced graphene oxide (rGO) films and rGO/MoS2 hybrid films were fabricated on polyethylene naphthalate substrates by a simple self-assembly method, which yielded flexible devices for detection of formaldehyde (HCHO) at room temperature. The sensing test results indicated that the rGO and rGO/MoS2 sensors were highly sensitive and fully recoverable to a ppm-level of HCHO. The bending and fatigue test results revealed that the sensors were also mechanically robust, durable and effective for long-term use. The rGO/MoS2 sensors showed higher sensitivities than rGO sensors, which was attributed to the enhanced HCHO adsorption and electron transfer mediated by MoS2 . Furthermore, two kinds of MoS2 nanosheets were prepared by either hydrothermal synthesis or chemical exfoliation and were compared for their detection of HCHO, which revealed that the hydrothermally produced MoS2 nanosheets with rich defects led to enhanced sensitivity of the rGO/MoS2 sensors. Moreover, these fabricated flexible sensors can be applied for the HCHO detection in food packaging.